O cinema como instância educativa e sua influência no empoderamento e na representação da mulher : uma análise do filme Capitã Marvel - Marques, Jamyle Massim (2021)
This dissertation articulates gender, education, and cinema. Gender studies analyze social construction and show how relationships between people are affected in their educational processes. In this context, cinema is an educational institution that promotes culture and influences the construction of identities through its representations. In order to analyze these issues, the film Captain Marvel (CM) was chosen for study, analyzed through the perspective of Cultural Studies with Feminist Hermeneutics. The central question was how cinema can influence gender representations and stereotypes, helping or not assisting women's empowerment process. The analysis of the film was carried out through the selection of some clippings from twelve scenes of this one and, in addition, four reviews were chosen, two from Brazil, one from the USA and one from Argentina published on websites, verifying which ones reaffirm or not, stereotypes of genre. From the analysis of the twelve scenes and the four reviews, it is possible to observe that the gender relations and the empowerment of the character and women in the film portray that despite showing timidly feminist issues, they present a representation of the woman further from the patriarchal model, however, there is still a lack of representativeness and appreciation of minorities. The choice of the CM film challenged reflections on issues of gender, race and class and on the empowerment of women, questioning the representations constructed by cultural artifacts centered on patriarchal stereotypes. It is possible to notice that among the people who criticize the film, there is little representativeness of the diversities and this also, in a certain way, influences the way the audience perceives the representations and reflections that the film suggests. The dissertation concludes that the representations exposed in the media, in favor of other representativeness and diversity, need to be discussed through the knowledge that the feminist movement offers to society.